Synergistic effects of rare variants of ARHGAP31 and FBLN1 in vitro in terminal transverse limb defects - Tian, Hong; Chu, Fan; Li, Yingjie; Xu, Mengmeng; Li, Wenjiao; Li, Chuanzhou (Frontiers in Genetics, 2022)
Background Aplasia cutis congenita (ACC) and terminal transverse limb defects (TTLD) are the most common features of Adams-Oliver syndrome (AOS). ARHGAP31 is one of the causative genes for autosomal dominant forms of AOS, meanwhile its variants may only cause isolated TTLD. Here we report a proband presented with apparent TTLD but not ACC. Methods Whole exome sequencing (WES) and sanger sequencing were applied to identify causative genes. Expression vectors were constructed for transfections in mammalian cell cultures followed by biochemical and functional analysis including immunoblotting, immunofluorescence staining and , cell counting kit-8 assay, etc. Results WES and Sanger sequencing suggested that the proband inherited novel rare ARHGAP31 variant (c.2623G>A (p.Glu875Lys)) and a novel rare FBLN1 variant (c.1649G>A (p.Arg550His)) from one of her asymptomatic parents respectively. Given FBLN1 variation has also been linked to syndactyly, we suspected that the two genes together contributed to the TTLD phenotype and explored their possible roles in vitro. Mutant FBLN1 showed consistently reduced protein expression resulted from impaired protein stability, whereas ARHGAP31 protein expression was only compromised when two mutants were co-transfectedunaltered by mutation. Moreover, fFunctional assays showed that only in the co-transfected group of two mutants cell viability was decreased, cell proliferation was impaired and apoptosis was activated, . Cdc42 activity was reduced decreaseddeclined by both ARHGAP31 mutation and FBLN1 mutation alone, and the two together. Furthermore, MAPK/ERK pathway was only activated by two mutants co-transfected group compared with two wild-type transfection. whereas in the presence of mutant ARHGAP31 activity of cell cycle regulator Cdc42 were elevated by mutant FBLN1 compared to the wild-type. Conclusion We report a case carrying two novel rare variants of limb defects associated genes, ARHGAP31 and FBLN1, and provide in vitro evidence that synergistic disruption of cellular functions attributed by the two mutants may potentiate the penetrance of clinical manifestations, expanding our knowledge of clinical complexity of causal gene interactions in TTLD and other genetic disorders.